A model of temporal scaling correctly predicts that motor timing improves with speed - Nicholas F. Hardy (Nature Portfolio, 2018)
Humans can perform complex motor movements at varying speeds. Here, the authors show that a recurrent neural network can be trained to exhibit temporal scaling obeying Weber’s law as well as validate a prediction of the model of improved precision of movements at faster speeds.